Application of Monte Carlo simulation and quantitative microbial risk approach to investigate seasonal variation of airborne particulate matter and bioaerosols in medical waste management department and wastewater treatment plant of Iranian hospitals - Mahbubeh Tangestani; Ahmad Jonidi Jafari; Majid Kermani; Roshanak Rezaei Kalantary; Hossein Arfaeinia (Results in Chemistry)
This study addresses a significant knowledge gap by conducting a thorough analysis of pollutants in hospital environments and utilizing advanced risk assessment models to evaluate their health impacts on workers for the first time. The study aimed to assess the concentration of particulate matter (PM1–2.5, PM0.5–1, PM0.25–0.5, and PM˂0.25) and bioaerosols (bacteria and fungi) in the air around waste disposal departments and wastewater treatment plants of selected hospitals in Bushehr city, Iran, during different seasons. A probabilistic risk assessment using Monte Carlo simulation and the Disability-Adjusted Life Years (DALYs) model was employed to evaluate the health risks of PM and bioaerosols on workers. The study collected 32 PM samples and 132 bioaerosol samples using a four-stage impactor and a single-stage Anderson sampler, respectively. The results showed that the highest concentration of PM was found in PM1–2.5, measuring 119.4 μg/m3, while bacteria and fungi concentrations were 617 and 756 CFU/m3, respectively. Additionally, larger PM sizes were more prevalent, and bacterial levels exceeded those of fungi in the wards. Waste disposal sections in hospitals exhibited higher pollution levels of PM, bacteria, and fungi compared to wastewater treatment plants, especially during summer. Bioaerosol levels exceeded existing standards in the surrounding air of these departments Risk values surpassed acceptable thresholds, indicating significant health concerns. Sensitivity analysis revealed that concentration (C) and exposure duration (ED) parameters had the most significant impact on worker health assessment.